Analysis of the entry mechanism of Crimean-Congo hemorrhagic fever virus, using a vesicular stomatitis virus pseudotyping system - Suda, Yuto; Fukushi, Shuetsu; Tani, Hideki; Murakami, Shin; Saijo, Masayuki; Horimoto, Taisuke; Shimojima, Masayuki (Archives of virology, 2016)
Crimean-Congo hemorrhagic fever (CCHF) is a tick-borne disease causing severe hemorrhagic symptoms with a nearly 30 % case-fatality rate in humans. The experimental use of CCHF virus (CCHFV), which causes CCHF, requires high-biosafety-level (BSL) containment. In contrast, pseudotyping of various viral glycoproteins (GPs) onto vesicular stomatitis virus (VSV) can be used in facilities with lower BSL containment, and this has facilitated studies on the viral entry mechanism and the measurement of neutralizing activity, especially for highly pathogenic viruses. In the present study, we generated high titers of pseudotyped VSV bearing the CCHFV envelope GP and analyzed the mechanisms involved in CCHFV infection. A partial deletion of the CCHFV GP cytoplasmic domain increased the titer of the pseudotyped VSV, the entry mechanism of which was dependent on the CCHFV envelope GP. Using the pseudotype virus, DC-SIGN (a calcium-dependent [C-type] lectin cell-surface molecule) was revealed to enhance viral infection and act as an entry factor for CCHFV.